THE DEVELOPMENT OF AN EDUCATIONAL PSYCHOLOGIST IN PROFESSIONAL ACTIVITY - Sergeeva, Marina; Dmitrichenkova, Svetlana; Kirillova, Tatyana; Lukashenko, Dmitry; Sokolova1, Aleksandra (Revista Inclusiones, 2020)
Professional activity of an educational psychologist includes psychological education, psychological prevention, psychological diagnostics, psychological correction, and psychological counseling as the main types of work. Each of these types might be primary depending on the problem the educational psychologist is addressing and the institution they work in. Professional calling is a complex phenomenon characterized by a complex of personal qualities of a professional and their social and psychological readiness to implement the functions of an educational psychologist as a helping profession specialist. The authors argue that the professional activity of an educational psychologist viewed as a helping profession specialist presents one of the most multifaceted and labor-intensive types of professional activity characterized by a variety of problems and tasks to be solved. For the structure and specific features of professional development phenomenon to be studied to the full extent, they must be correlated with the various aspects of professionalism and professional activity, primarily with the professionally important qualities that present a certain foundation for any profession reflecting both the requirements for the profession and the criteria for the success of professional development. The process of professional training of an educational psychologist should incorporate the innovative educational technologies that, according to the authors, promote professional training improvement